2015
DOI: 10.1002/ana.24534
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin and vitamin D for migraine prevention: A randomized, controlled trial

Abstract: Objective To assess efficacy and tolerability of simvastatin plus vitamin D for migraine prevention in adults with episodic migraine. Methods We performed a randomized, double-blind, placebo-controlled trial with a 12-week baseline period and 24-week intervention period in 57 adults with episodic migraine. Participants were randomly assigned to simvastatin 20 mg tablets twice daily plus vitamin D3 1000 international units capsules twice daily or matching placebo tablets and capsules. Results Compared to pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 50 publications
(35 reference statements)
2
58
0
2
Order By: Relevance
“…The role of vitamin D in headaches remains unclear, mainly due to predominantly small studies with inconsistent findings89101112131415161718 and the lack of large randomized supplementation trials that would show benefit after improvement of vitamin D status with vitamin D supplementation23. Our study, being one of the largest studies that have investigated the issue, supports the view that vitamin D may be beneficial in headache prevention.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The role of vitamin D in headaches remains unclear, mainly due to predominantly small studies with inconsistent findings89101112131415161718 and the lack of large randomized supplementation trials that would show benefit after improvement of vitamin D status with vitamin D supplementation23. Our study, being one of the largest studies that have investigated the issue, supports the view that vitamin D may be beneficial in headache prevention.…”
Section: Discussionsupporting
confidence: 66%
“…However, results from larger, randomized, placebo-controlled vitamin D supplementation trials have been mixed1516. Recently, combined therapy with simvastatin and vitamin D 3 reduced the number of days with migraine17. This finding supported the previous cross-sectional observation from the same study group that statin use was associated with lower odds for severe headache or migraine only among those with higher serum 25(OH)D concentrations18.…”
supporting
confidence: 75%
“…A few studies have also demonstrated beneficial effects of Vitamin D supplementation (with other drugs) in headache frequency and intensity,7 8 although a few conflicting observations have also been reported in the literature 18. The literature on the relation between vitamin D and tension-type headache is sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Choosing antihypertensive medications which improve endothelial function and prevent migraine, such as lisinopril, candesartan, and verapamil, should be considered. Statins in combination with Vitamin D were demonstrated to prevent migraine in a 2015 study, 101 in addition to their role in controlling lipid levels and decreasing inflammation. Non-pharmacological options that promote endothelial health while preventing migraine include exercise, meditation, and weight loss.…”
Section: Implications For Diagnosis and Treatmentmentioning
confidence: 99%